Efeitos da suplementação de vitamina D e treinamento físico aeróbico sobre a função muscular e composição corporal de pacientes em hemodiálise crônica - Vogt, Barbara Perez [UNESP] (2017)
Background: function and muscle mass depletion is frequent in hemodialysis patients, as well as vitamin D deficiency. Vitamin D supplementation exerts positive effects on muscles, and clinical trials combining vitamin D supplementation and physical training have promoted improvements on functional capacity and muscle quality in elderly. Objective: to assess the effects of vitamin D supplementation and intradialytic aerobic training (IDAT) on biochemical parameters, body composition, and muscle function in patients on maintenance hemodialysis. Methods: clinical trial with two arms: randomized, controlled, and double-blind for vitamin D, and randomized, controlled and open-label for IDAT. Patients were randomized in one of the four groups: vitamin D supplementation and IDAT, placebo and IDAT, vitamin D supplementation, and placebo. Muscle mass was assessed by dual-energy X-ray absorptiometry and muscle function was assessed by handgrip strength. Intervention lasted 16 weeks. IDAT program was performed using cycle ergometer, three times a week during hemodialysis session. Vitamin D supplementation was cholecalciferol 50,000 IU per week and vitamin D status was evaluated by serum 25-hydroxyvitamin D (25(OH)D) levels. Results: twenty-nine patients were enrolled in this trial. Nine were excluded during the intervention. Serum vitamin D significantly rose in both groups supplemented with cholecalciferol (baseline: 30.1 ± 6.26 ng/ml; post-intervention: 41.3 ± 9.85 ng/ml; p<0.001). There was a significant interaction between interventions improving triglycerides and HDL-cholesterol. There was significant correlation between variation of serum 25(OH)D and CRP, and variation of serum 25(OH)D and handgrip strength. Vitamin D supplementation had a significant effect on the increase of handgrip strength and BMI. It was not possible to identify whether this weight gain corresponded to lean mass or body fat, since both presented no differences among groups. Conclusion: cholecalciferol supplementation and IDAT interacted improving lipid profile in maintenance hemodialysis patients. Cholecalciferol supplementation promoted muscle function improvement and body weight gain.